2020
DOI: 10.3390/ma13030641
|View full text |Cite
|
Sign up to set email alerts
|

Self-Etch Silane Primer: Reactivity and Bonding with a Lithium Disilicate Ceramic

Abstract: The aim of the study was to evaluate the stability, reactivity, and bond strength with a lithium disilicate ceramic of a self-etch silane primer (Monobond Etch and Prime/MEP). The stability was evaluated by 1H-,31P-NMR spectroscopy (before/after aging), and the reactivity by micro MIR-FTIR spectroscopy on Ge surfaces (0, 1, 24 h) using a prehydrolyzed silane primer (Calibra Silane Coupling Agent/CLB), as a control. The effect of MEP vs. 5% HF-etching on ceramic roughness was assessed by optical profilometry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…It was demonstrated that the bonding mechanism of EP is related to the interaction of phosphoric monomers and ceramic ions rather than the methacrylate silane bonding to the glass ceramic. After aging, the self-etching silane primer was stable, retaining the original silanol activity; however, the stability of the phosphate comonomer was affected, leading to values even lower than those of the negative control (HF-etched substrate without silane) [33]. In the current study, we tested SBS immediately after storing the samples at room temperature for 24 h without thermocycling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was demonstrated that the bonding mechanism of EP is related to the interaction of phosphoric monomers and ceramic ions rather than the methacrylate silane bonding to the glass ceramic. After aging, the self-etching silane primer was stable, retaining the original silanol activity; however, the stability of the phosphate comonomer was affected, leading to values even lower than those of the negative control (HF-etched substrate without silane) [33]. In the current study, we tested SBS immediately after storing the samples at room temperature for 24 h without thermocycling.…”
Section: Discussionmentioning
confidence: 95%
“…Schestatsky et al showed that surface treatment with EP led to similar fatigue performance when compared to HF + silane application for both CAD and Press processing techniques, but it tended to provide higher mechanical reliability [30]. On the other hand, Dimitriadi et al demonstrated a significantly lower SBS with EP in all treatments/storage conditions in comparison to HF + silane [33]. When HF was used without silane, similar SBS values were recorded after storage in distilled water at 37 • C for 1 week, but after thermocycling (5000 × 5 • C-55 • C, 20 s dwell time) or accelerated aging conditions (immersion in 100 • C water for 24 h), EP showed even significantly lower SBS than HF without silane.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved mainly in bonding to dental ceramics and composites are micro-mechanical interlocking and chemical binding [2][3][4]. Micro-mechanical interlocking can be obtained by either etching glass-rich ceramics, commonly using hydrofluoric-acid (HF), or by sandblasting, which is preferentially recommended to provide micro-mechanical interlocking at the surface of composite CAD/CAM blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Most commercial one-bottle and thus silane-coupling primers are supplied in a water-free solvent, upon which the silane is activated when clinically applied. To avoid having to use the rather caustic HF, even not used in certain countries, and to simplify ceramic-bonding procedures, combined etching and silanization has more recently been made possible with the introduction of Monobond Etch & Prime (Ivoclar Vivadent, Schaan, Liechtenstein) [2,3,8]. Previous research showed that silane-containing so-called 'universal' adhesives did not have enough silane-coupling effect [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, HF can be toxic to the human body as well as the environment-imprudent users run the risk of suffering from acute and chronic symptoms [9,10]. To simplify the pretreatment, a new self-etching ceramic primer is proposed in this study, which can be used to replace the aforementioned process with a safer, onestep protocol [11,12]. This process, which conducts etching and salinization simultaneously, serves as a viable alternative to the classic protocol.…”
Section: Introductionmentioning
confidence: 99%